2016
DOI: 10.1002/cncr.30493
|View full text |Cite
|
Sign up to set email alerts
|

Radiation therapy dose is associated with improved survival for unresected anaplastic thyroid carcinoma: Outcomes from the National Cancer Data Base

Abstract: Background We assessed the outcomes of patients with unresected anaplastic thyroid carcinoma (ATC) in the National Cancer Data Base (NCDB) and explored potential relationships between radiation therapy (RT) dose and overall survival (OS). Methods The study group was composed of patients who received either no surgery or grossly incomplete resection. Correlates of OS were explored using univariate and multivariable analysis (MVA) analyses. Results A total of 1,288 patients were analyzed. Mean age was 70.2 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 33 publications
5
53
0
1
Order By: Relevance
“…Median OS was 5.9 vs 9.9 months (surgery + RT with or without chemotherapy) for stage IVB disease; here, we reported median OS of 4.7 vs 7.9 months for the subgroups receiving definitive surgery + RT +/− chemotherapy. Finally, Pezzi et al evaluated the impact of radiotherapy dose in a primarily unresected ATC population . Higher radiotherapy dose was significantly linked to longer OS in a multivariable model; and also demonstrated in PSM‐cohorts comparing 45‐59 Gy vs 60‐75 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…Median OS was 5.9 vs 9.9 months (surgery + RT with or without chemotherapy) for stage IVB disease; here, we reported median OS of 4.7 vs 7.9 months for the subgroups receiving definitive surgery + RT +/− chemotherapy. Finally, Pezzi et al evaluated the impact of radiotherapy dose in a primarily unresected ATC population . Higher radiotherapy dose was significantly linked to longer OS in a multivariable model; and also demonstrated in PSM‐cohorts comparing 45‐59 Gy vs 60‐75 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…4 Gy was an independent predictor for OS in 3,552 patients. Pezzi et al [11] similarly compared three total dose groups, < 45 Gy, 45-59.9 Gy, and 60-75 Gy, in patients with unresected ATC, and reported that a total dose of 60-75 Gy was an independent predictor for OS in 2,987 patients. Based on the results of those studies and ours, a higher dose of radiation is important for the OS of ATC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The median OS in their study was 9.3 months. Glaser et al [10] and Pezzi et al [11] reported that radiotherapy with a high total dose improved the OS of ATC patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not certain, as to which cumulative doses and whether radiotherapy vs combined radiochemotherapy before or after surgery is beneficial. A recent large analysis of 1288 patients from the NCDB including patients with non-resected ATC survival was significantly better in patients with radiotherapy with a cumulative dose of >45 Gy compared to no radiotherapy or less than 45 Gy (Pezzi et al 2017).…”
Section: Radiotherapymentioning
confidence: 99%